2020
DOI: 10.1177/1538574420983652
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Clinical Characteristics and Early Outcomes of Type B Aortic Dissection Patients With Thoracic Endovascular Aortic Repair

Abstract: Objective/Background: This study examined the 10-year hospitalization characteristics, economic patterns and early clinical outcomes of type B aortic dissection (TBAD) patients that underwent thoracic endovascular aortic repair (TEVAR) in one high-volume hospital in China. Methods: We performed a population-based retrospective analysis based on electronic medical record system data provided by Zhongshan Hospital Fudan University from 2009 to 2018. Results: We identified 1,367 cases of TBAD patients with TEVAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Most patients in our TBAD cohort were male, most had hypertension, and few of them had diabetes. These population characteristics are consistent with the reported TBAD in the Chinese population (Huang et al, 2021). Based on whole genome sequencing data, we demonstrated that the ULK4 gene is associated with the age of TBAD onset based on both the SKAT and 2-sample MR analyses.…”
Section: Discussionsupporting
confidence: 89%
“…Most patients in our TBAD cohort were male, most had hypertension, and few of them had diabetes. These population characteristics are consistent with the reported TBAD in the Chinese population (Huang et al, 2021). Based on whole genome sequencing data, we demonstrated that the ULK4 gene is associated with the age of TBAD onset based on both the SKAT and 2-sample MR analyses.…”
Section: Discussionsupporting
confidence: 89%
“…[8][9][10] This is further affected by the majority of observational cohort studies originating from high volume, specialized centres with results that may not always be generalizable. 13,17 The present analyses of a comprehensive national dataset, as well as population-based data, reflects comprehensive and generalizable outcomes. The authors have identified relatively low operative mortality following intervention for TBAD in the setting of increasing admissions and procedure rates.…”
Section: Discussionmentioning
confidence: 99%
“…This trend appears to be consistent with other studies. 17 The reasons for the observed advances are unclear, but may include better and prompter medical management, enhanced surgical case selection and timing of intervention, as well as improving stent technology and increasing technical expertise. Not surprisingly, several post-intervention complications were more common following OAR compared to TEVAR.…”
Section: Discussionmentioning
confidence: 99%